2002
DOI: 10.3727/000000002783985422
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Treatment of Mice Recipients Preserves β-Cell Function in Porcine Islet Transplantation

Abstract: Encapsulation of islets of Langerhans confers protection against cell-mediated immune destruction and so should allow the transplantation of islets without immunosuppression. Xenotransplantation of encapsulated islets of Langerhans might therefore help overcome problems of human organ donor shortage. Given that islets exposed to sustained hyperglycemia show impaired β-cell function, we set out to determine whether recipient treatment with insulin could improve transplantation success rate. Islets of Langerhans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…β-Cell apoptosis peaks around day 3 after transplantation and plays a major role in this early β-cell death (5,11). The cause of the initial β-cell apoptosis is multifactorial (12), with hypoxia playing a fundamental role (10), and other factors such as anoikis (47), nonspecific inflammation (29,38,46), and hyperglycemia (5,15,26,33) also contributing to islet damage. Several strategies that have successfully increased the long-term outcome of islet transplantation have been, however, unable to increase the initial survival of islets (11).…”
Section: Discussionmentioning
confidence: 99%
“…β-Cell apoptosis peaks around day 3 after transplantation and plays a major role in this early β-cell death (5,11). The cause of the initial β-cell apoptosis is multifactorial (12), with hypoxia playing a fundamental role (10), and other factors such as anoikis (47), nonspecific inflammation (29,38,46), and hyperglycemia (5,15,26,33) also contributing to islet damage. Several strategies that have successfully increased the long-term outcome of islet transplantation have been, however, unable to increase the initial survival of islets (11).…”
Section: Discussionmentioning
confidence: 99%
“…In neonatal rat islet grafts, Hayek et al reported that poorly controlled diabetes by only a small amount of insulin therapy had a cure rate of only 30%, whereas it increased to 100% in strictly controlled diabetic rats by a previous islet transplant [28]. It has also been shown that treatment of mice with daily insulin injections had a beneficial effect on transplanted adult islets [29][30][31]. Brown et al reported that diabetes was cured by transplanting a single fetal pancreas with insulin treatment in rats [32].…”
Section: Discussionmentioning
confidence: 99%
“…fibers (2,9,20). The mean cut-off weight of the fibers is Since the work of Patience, it has been established that 70-100 kDa, 5-10 nm according to the manufacturer's PERVs secreted by PK15 and Shimozuma cell lines inestimate.…”
Section: Fibers and Encapsulationmentioning
confidence: 99%
“…After encapsulation, cells were maintained in culture. We verified cell proliferamoglycemia in diabetic mice following the transplantation of porcine islets encapsulated in AN69 fibers (2,9,20).…”
Section: Introductionmentioning
confidence: 99%